Hak Masyarakat Adat - Zalsabillah, Annisa; Dahlan, Darnia; Anugrah, Abdi; Taqyuddin, Andi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Constitutional recognition and protection of indigenous peoples remains recognized after the 1945 Constitution was amended, where this is regulated in Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution. Although there is constitutional recognition and protection of indigenous peoples, there are still two main problems that have not been resolved. First, the recognition of indigenous peoples is enforced with certain conditions, namely as long as the indigenous peoples still exist, develop in accordance with the progress of the times, and in accordance with the principles of the Unitary State of the Republic of Indonesia (NKRI). These conditions come from provisions in lower laws, and in practice often become obstacles in providing recognition and protection of the rights of indigenous peoples. The phrase